The Experience of Workplace Politics - Gandz, Jeffrey; Murray, Víctor (Academy of Management Journal, 1980)
This study investigates the perceived politicization of organizational processes and their attitudes and beliefs about workplace politics. Perceived politicization is related to characteristics of respondents' jobs, their employing organizations, and demographic variables. It is proposed that perceived politicization may be one dimension of overall job satisfaction.